Hesperetin Inhibits Vascular Formation by Suppressing of the PI3K/AKT, ERK, and p38 MAPK Signaling Pathways - Kim, Gi Dae (Prev Nutr Food Sci, 2014)
Hesperetin has been shown to possess a potential anti-angiogenic effect, including vascular formation by endothelial cells. However, the mechanisms underlying the potential anti-angiogenic activity of hesperetin are not fully understood. In the present study, we evaluated whether hesperetin has anti-angiogenic effects in human umbilical vascular endothelial cells (HUVECs). HUVECs were treated with 50 ng/mL vascular endothelial growth factor (VEGF) to induce proliferation as well as vascular formation, followed by treatment with several doses of hesperetin (25, 50, and 100 μM) for 24 h. Cell proliferation and vascular formation were analyzed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and tube formation assay, respectively. In addition, cell signaling related to cell proliferation and vascular formation was analyzed by western blot. Furthermore, a mouse aorta ring assay was performed to confirm the effect of hesperetin on vascular formation. Hesperetin treatment did not cause differences in HUVECs proliferation. However, hesperetin significantly inhibited VEGF-induced cell migration and tube formation of HUVECs (P<0.05). Moreover, hesperetin suppressed the expression of ERK, p38 MAPK, and PI3K/AKT in the VEGF-induced HUVECs. In an ex vivo model, hesperetin also suppressed microvessel sprouting of mouse aortic rings. Taken together, the findings suggest that hesperetin inhibited vascular formation by endothelial cells via the inhibition of the PI3K/AKT, ERK and p38 MAPK signaling.